PENYULUHAN KEAMANAN PANGAN PADA KEDAI KOPI DI SURABAYA DI MASA PANDEMI COVID - 19 - Latifahtur Rahmah; Angeline Listiyani Utomo; Go Fernando Wibisono (Institute of Research and Community Outreach - Petra Christian University, 2021)
Food industry personnel, including coffee shops, do not have the opportunity to work from home and are required to continue working at work as usual. By holding outreach on food safety keeping all workers in food production and supply chains healthy and safe is critical to surviving the current pandemic. Maintaining the movement of food along the food chain is an important function that needs to be contributed by all stakeholders along the food chain. The purpose of this community service is to increase knowledge or information about food safety for food or beverage handlers so that coffee shops are better prepared to deal with COVID-19 conditions. To facilitate the communication of counseling using poster, and divided the discussion of food safety into 4, namely: 1) food safety of producers; 2) food safety distributors; 3) food safety of consumers 4) Food safety of food production. After being given counseling, an evaluation was carried out by measuring employee knowledge using a comparison of pre-test and post-test questionnaires given through the google form. The results of the evaluation stated that all employees in the eight coffee shops had increased knowledge about food safety. Most of the employees felt that community service activities with counseling were useful for maintaining security in coffee shops so that they could make employees and customers feel safe and comfortable. Abstrak: Insan industri makanan, termasuk kedai kopi, tidak memiliki kesempatan untuk bekerja dari rumah dan diharuskan untuk tetap bekerja di tempat kerja seperti biasa. Dengan mengadakan sosialisasi tentang keamanan pangan, menjaga semua pekerja dalam produksi pangan dan rantai pasokan tetap sehat dan aman sangat penting untuk bertahan dari pandemi saat ini. Menjaga pergerakan makanan di sepanjang rantai makanan merupakan fungsi penting yang perlu disumbangkan oleh semua pemangku kepentingan di sepanjang rantai makanan. Pengabdian kepada masyarakat ini bertujuan untuk menambah pengetahuan atau informasi tentang keamanan pangan bagi penjamah makanan atau minuman sehingga warung kopi lebih siap menghadapi kondisi COVID-19. Untuk memudahkan komunikasi, penyuluhan menggunakan poster dan membagi pembahasan keamanan pangan menjadi 4, yaitu: 1) keamanan pangan produsen; 2) distributor keamanan pangan; 3) keamanan pangan konsumen 4) Keamanan pangan produksi pangan. Setelah diberikan penyuluhan, dilakukan evaluasi dengan mengukur pengetahuan karyawan menggunakan perbandingan kuesioner pre-test dan post-test yang diberikan melalui google form. Hasil evaluasi menyatakan bahwa seluruh karyawan di delapan kedai kopi tersebut mengalami peningkatan pengetahuan tentang keamanan pangan. Sebagian besar karyawan merasa kegiatan pengabdian masyarakat dengan penyuluhan bermanfaat untuk menjaga keamanan di warung kopi sehingga dapat membuat karyawan dan pelanggan merasa aman dan nyaman.